The future competitiveness of the non-Emissions Trading Scheme district heating systems in the Baltic States. (15th January 2016) - Ziemele, Jelena; Pakere, Ieva; Blumberga, Dagnija
Highlights: Optimal efficiency scenarios for non-ETS district heating (DH) system are proposed. A multi-criteria model is developed to determine efficiency rating of the DH system. Analyses development of DH system with an aim of reduced greenhouse gas emissions. Heat tariff and emissions reduce when shifting from fossil fuel to wood. The desirable scenarios for different stakeholders are controversial. Abstract: This paper is devoted to the development of the non-Emissions Trading Scheme for the district heating systems. To select indicators characterizing overall operation of the non-Emissions Trading Scheme district heating system, the article analyses various aspects (type of fuel, temperature regime, level of building energy efficiency) that impact the development of a district heating system model, which strives to reach 4th generation district heating system and to reduces greenhouse emission gases. To determine efficiency rating of the district heating system, a multi-criteria model is developed using selected indicators. The most suitable temperature regime of district heating systems is analyzed for a new buildings and exiting dwelling area depending on end-user heat energy consumption. Research methodology includes algorithm with several modules. The multi-criteria analysis evaluates different district heating systems and identifies optimal solution of 12 scenarios taking into account different criteria. The TOPSIS tool is integrated to find the optimal solutions. Results of the multi-criteria analysis confirm that scenario that is the closest to the ideal solution from the point of view of district heating company, sharply differs from the best scenario of the developers. From the point of view of district heating company the optimal solution is the lowest temperature regime 60/30 and wood chips as energy source.